Students’ Challenges and Solutions of Using AI-based Tools for Academic Writing - Nugroho, Ribka Anastasia; Trisusana, Anis (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2025)
The use of AI in the education field has become common, especially in academic writing. However, students faced many of the challenges in using AI for academic writing. This study aims to discover the students’ challenges and solutions in using AI-based tools for academic writing. The research method used was a descriptive qualitative design. The research instruments were structured questionnaires and semi-structured Interviews. An investigation of students’ challenges and solutions of using AI-based tools for academic writing revealed some findings. Every students using different AI in each of the writing stages for their academic writing such as ChatGPT, Quillbot, Grammarly, etc. Moreover, the students’ challenges in using AI for academic writing were divided into 3 categories: ethical consideration, bias and inaccuracy results, and limited features. Meanwhile, the students’ solutions in using AI for academic writing were divided into four categories: double-check result from AI, Train algorithm, purchasing the premium version, and human role to keep the originality. The researcher suggested that the topics of the students strategy in using AI for academic writing is spotlighted in the further studies